Improving Elementary School Students’ Critical Thinking Skills Through Wordwall-Based Learning Integrated with Banyumas Local Wisdom - Pamungkas, Bekti Kuat; Wakhudin (Journal of Innovation and Research in Primary Education, 2026)
This article aims to analyze the improvement of elementary school students’ critical thinking skills through science learning using word walls and integrated with Banyumas local wisdom. This research is descriptive qualitative research with an ethnopedagogical approach and case study method. The research uses data obtained from observation, interviews, and documentation studies. The data came from 100 fourth-grade students from four schools in the Kencana Cluster. The data was then analyzed using Miles and Huberman’s triangulation model. Data validity was determined through credibility, transferability, dependability, and confirmability. The results showed that the initial critical thinking skills were in the adequate category. The weaknesses were mainly in the basic support and conclusion drawing indicators. After learning science using word walls integrated with Banyumas local wisdom, there was an increase in the informants’ involvement in learning. Teachers also stated that students were better able to give reasons, connect the context of the material with Banyumas local wisdom, and conclude information more accurately. The findings of this study indicate that Wordwall integrated with Banyumas local wisdom improves the critical thinking skills of elementary school students. This study emphasizes the importance of integrating local wisdom into science learning, which is an implementation of Merdeka Belajar (Freedom of Learning). However, this study has limitations in terms of the number of informants and was only conducted in one subject. It is recommended to expand the sample and test Wordwall in other subjects.